Method for manufacturing carbon-containing slide plate refractory

By incorporating titanium carbide and metallic titanium and heat-treating in a nitrogen atmosphere, the method enhances the corrosion and hydration resistance of slide plate refractories, ensuring improved performance in steel smelting applications.

JP7610109B2Active Publication Date: 2025-01-08SHINAGAWA REFRACTORIES CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021028611
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-25
Publication Date
2025-01-08
Estimated Expiration
2041-02-25

AI Technical Summary

Technical Problem

Existing carbon-containing slide plate refractories suffer from insufficient hydration and corrosion resistance, particularly when stored in humid conditions or used in multi-furnace casting of Ca-treated steel.

Method used

A method involving the addition of titanium carbide and/or metallic titanium to the refractory mixture, followed by heat treatment in a nitrogen atmosphere with a nitrogen partial pressure of 0.85 atm or more, generates a nitrogen-containing phase that enhances corrosion and hydration resistance by reducing pore size and increasing the refractory's density.

Benefits of technology

The method produces a carbon-containing slide plate refractory with improved mechanical strength, spalling resistance, and enhanced corrosion and hydration resistance, suitable for use in steel smelting processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610109000009
    Figure 0007610109000009
  • Figure 0007610109000001
    Figure 0007610109000001
  • Figure 0007610109000002
    Figure 0007610109000002
Patent Text Reader

Abstract

To provide a method for producing a carbon-containing slide plate refractory securing sufficient mechanical strength and spalling resistance, and simultaneously, having higher hydration resistance and corrosion resistance.SOLUTION: A method for producing a carbon-containing slide plate refractory has a process in which a molded body for a slide plate comprising titanium carbide and / or metallic titanium by 0.5 to 8 mass% in outer percentage to the main raw material composed of a refractory aggregate and carbonaceous raw material is heat-treated at 400 to 1,400°C in a nitrogen atmosphere having a nitrogen partial pressure of 0.85 atm or more with the conversion of the total atmospheric pressure to 1 atm in heat treatment under the atmospheric pressure.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a carbon-containing slide plate refractory material used for controlling the flow rate of molten steel in a steel smelting process. [Background technology]

[0002] In steel smelting, slide plate refractories are commonly used to control the flow rate of molten steel. Two or three slide plate refractories with inner holes are stacked on top of each other, restrained, and subjected to surface pressure, and the opening of the holes is adjusted by sliding the slide plate refractories. The slide plate refractories used under such severe conditions must have all the following: mechanical strength to withstand restraint and surface pressure, spalling resistance to withstand sudden thermal shock when receiving steel, and corrosion resistance to erosion by molten steel.

[0003] First, in order to ensure the spalling resistance of the slide plate refractory, it is common to make the slide plate refractory contain carbon. That is, refractory materials that contain carbon are generally used to make the slide plate refractory. Here, for example, alumina, spinel, magnesia, zirconia, etc. are used as the aggregate raw material that makes up the refractory material, and alumina is particularly used.

[0004] However, refractory materials consisting only of aggregate raw materials and carbon have the problem that the strength of slide plate refractory made of such refractory materials is low because the bonds between the raw material particles are formed only by carbon bonds. To address this problem, it is known that adding metallic silicon to refractory materials is effective. This is because ceramic bonds such as silicon carbide and silicon oxide (silica), which have stronger binding strength than carbon bonds, are formed inside the slide plate refractory during heat treatment (or firing).

[0005] For example, Patent Document 1 discloses a plate refractory for a sliding nozzle, which is formed of 5-20% by weight of carbonaceous raw material, 3-10% by weight of metal silicon, 1-20% by weight of zirconia raw material, and the remainder being neutral and / or basic refractory raw material. However, a part of the metal silicon blended in the plate refractory for a sliding nozzle reacts with the carbonaceous raw material in the plate refractory to form silicon carbide, but both the metal silicon and the silicon carbide are converted to silica during the use of the plate refractory. Since the corrosion resistance of silica against molten steel is low, there is a problem that the added metal silicon significantly reduces the corrosion resistance of the plate refractory against molten steel types that are prone to molten refractory damage, such as high manganese steel, high oxygen steel, and calcium-treated steel.

[0006] To address this problem, the addition of metallic aluminum to slide plate refractories has been proposed. This is because the added metallic aluminum eventually changes to alumina, which has significantly higher corrosion resistance to molten steel than silica. However, when a slide plate refractory containing added metallic aluminum is heat treated, the added metallic aluminum reacts with carbon to produce aluminum carbide, which is easily hydrated. If the amount of aluminum carbide produced increases, the slide plate refractory has a disadvantage that its hydration resistance decreases, hydration occurs inside the slide plate refractory during storage, and cracks occur, making it unusable.

[0007] Various proposals have been made to suppress the formation of aluminum carbide in the slide plate refractory containing metallic aluminum as described above and to improve the hydration resistance of the slide plate refractory.

[0008] For example, Patent Document 2 discloses an alumina-carbon slide gate plate which is characterized in that the refractory raw material is made of an alumina refractory aggregate and a carbon-containing raw material with a carbon content of 1 to 10 mass % and contains an Al-Si alloy of 1 to 15 mass % on an outer percentage basis, and is subjected to a firing treatment at a temperature range exceeding 1000°C and up to 1500°C.

[0009] Patent Document 3 discloses a method for manufacturing a plate for a slide gate, which comprises kneading and molding a mixture of a fire-resistant raw material, a phenolic resin, and an aluminum powder consisting of spherical atomized powder, and then heat-treating the mixture at a temperature of 550 to 650°C.

[0010] Furthermore, Patent Document 4 discloses a plate for a slide gate, which is characterized by being made of a sintered refractory material obtained by kneading, molding, and sintering a 100% mixture of raw materials consisting of (A) 73% or more and 96% or less by weight of refractory aggregate made of one or more types of refractory inorganic materials, (B) 0.1% or more and 0.5% or less by weight of fibrous aluminum metal, (C) 1% or more and 5% or less by weight of flaky aluminum metal powder, (D) 2% or more and 10% or less by weight of carbonaceous powder, and (E) 0.1% or more and 5% or less by weight of metal silicon powder, to which is added an external thermosetting resin of 3% or more and 10% by weight as a binder.

[0011] However, the slide plate refractories disclosed in Patent Documents 2 to 4 have problems in that they are insufficient in hydration resistance during long-term storage and also insufficient in corrosion resistance to calcium-treated steel.

[0012] In order to address this problem, for example, Patent Document 5 discloses a slide plate refractory that is characterized by containing a refractory material made of refractory aggregate and a carbonaceous raw material, and an aluminum-chromium alloy.

[0013] Furthermore, Patent Document 6 discloses a slide plate refractory comprising a refractory material made of a refractory aggregate and a carbonaceous raw material, and an aluminum-chromium-silicon based metal additive.

[0014] Patent Document 7 also describes a method for producing a molded body by kneading a mixture of 60 to 97.4 mass% of a refractory inorganic material, 1 to 10 mass% of a carbonaceous material, 0.5 to 12 mass% of Al or an Al-containing alloy, 0.1 to 10 mass% of a nitride in which the standard Gibbs energy of formation per mole of nitrogen atom in the nitride at the maximum temperature during heat treatment is greater than the standard Gibbs energy of formation of AlN and is negative, and 1 to 8 mass% of a binder, and forming the molded body into a predetermined shape. A method for producing a carbon-containing refractory plate for a sliding nozzle, characterized by heat treatment at a maximum temperature of 800 to 1400°C in a non-oxidizing atmosphere containing 0.01% by volume or less (Claim 1); and one or more nitrides having a standard Gibbs energy of formation per mole of nitrogen atom in the nitride at the maximum temperature during heat treatment that is greater than the standard Gibbs energy of formation of AlN and is more negative are disclosed, which are selected from the group consisting of Si3N4, Mg3N2, BN, CrN and CrN2 (Claim 2).

[0015] Furthermore, Patent Document 8 discloses that, for the purpose of providing a sliding nozzle plate having excellent heat spalling resistance and improved oxidation resistance, at least one refractory aggregate raw material such as alumina, silica, zirconia, magnesia, spinel, etc., 0.2 to 10.0% by weight of expanded graphite, and 0.1 to 8.0% by weight of at least one metal as an oxidation inhibitor are added (Claim 1); and further, at least one carbide such as ZrC, TiC, SiC, B4C, etc. or boride such as TiB2, ZrB2, AlB2 is added in an amount of 0.05 to 10.0% by weight as the oxidation inhibitor (Claim 2, paragraph

[0014] ). [Prior art documents] [Patent documents]

[0016] [Patent Document 1] Japanese Patent Application Publication No. 58-99161 [Patent Document 2] JP 2012-192430 A [Patent Document 3] JP 2000-94121 A [Patent Document 4] Japanese Patent Application Publication No. 11-199313 [Patent Document 5] JP 2018-114507 A [Patent Document 6] JP 2018-144088 A [Patent Document 7] JP 2017-190254 A [Patent Document 8] JP 2003-245770 A Summary of the Invention [Problem to be solved by the invention]

[0017] However, in the slide plate refractories disclosed in Patent Documents 5 to 8, although the hydration resistance and corrosion resistance are improved, the hydration resistance of the slide plate refractory is insufficient when stored for a long period of time in a humid place, and the corrosion resistance of the slide plate refractory is insufficient when Ca-treated steel is cast in multiple furnaces.

[0018] It is therefore an object of the present invention to provide a method for producing a carbon-containing slide plate refractory having sufficient mechanical strength and spalling resistance while at the same time having higher hydration and corrosion resistance. [Means for solving the problem]

[0019] In order to carry out various investigations on carbon-containing slide plate refractories to which titanium carbide and / or metallic titanium have been added, the inventors of the present invention press-molded mixtures of various raw materials, obtained molded bodies, and heat-treated them under various conditions. As a result of evaluating the properties of the slide plate refractories after the heat treatment, the inventors have obtained the following findings.

[0020] For example, when a molded body for a carbon-containing slide plate refractory to which titanium carbide and / or metallic titanium are added is heat-treated in a nitrogen atmosphere with a nitrogen partial pressure of 0.85 atm or more when converted to a total pressure of 1 atm, titanium carbide and metallic titanium can easily take up nitrogen in the atmosphere, and a nitrogen-containing phase containing titanium nitride such as titanium carbonitride or titanium nitride and containing 1 to 20 mass% of nitrogen element (hereinafter collectively referred to as "nitrogen-containing phase") can be generated in situ, and both the corrosion resistance and hydration resistance of the resulting slide plate refractory to molten steel can be significantly improved. The generation of the nitrogen-containing phase can be confirmed by electron probe microanalyzer (EPMA) analysis.

[0021] The reason for the improved corrosion resistance to molten steel is that the in-situ generation of the nitrogen-containing phase reduces the number of pores in the slide plate refractory, reduces the pore size, and makes the refractory structure denser. In addition, the nitrogen-containing phase itself is less likely to dissolve in molten steel and liquid inclusion slag in molten steel. Even if a small amount of the nitrogen-containing phase dissolves, the viscosity of the molten steel and liquid inclusion slag can be significantly increased, making it difficult for the molten steel and liquid inclusion slag to penetrate into the slide plate refractory.

[0022] The reasons for the improved hydration resistance of the slide plate refractory are considered to be as follows: First, when metallic aluminum is not added, aluminum carbide is not generated, and the nitrogen-containing phase is not hydrated, so the slide plate refractory is not hydrated. Also, when titanium carbide and / or metallic titanium are used in combination with metallic aluminum, metallic aluminum constantly absorbs nitrogen from the atmosphere through the nitrogen-containing phase that has already been generated during heat treatment, and changes to aluminum nitride, so that the generation of aluminum carbide is suppressed, and the nitrogen-containing phase generated in situ is very active, so that nitrogen is likely to move from the atmosphere to metallic aluminum via the nitrogen-containing phase. As a result, even when titanium carbide and / or metallic titanium are used in combination with metallic aluminum, the slide plate refractory is not hydrated.

[0023] On the other hand, even if a slide plate molding containing aluminum metal but not titanium carbide and / or titanium metal is heat-treated in the same nitrogen atmosphere, the aluminum metal is unlikely to change to aluminum nitride. Even if the aluminum metal does change to aluminum nitride, the amount of aluminum nitride produced is very small, and most of the aluminum metal changes to aluminum carbide, which is easily hydrated.

[0024] Based on the above findings, the present inventors have completed the present invention. That is, the present invention provides a method for producing a carbon-containing slide plate refractory, comprising the steps of: Refractory aggregate made of alumina and alumina-zirconia or made of alumina, alumina-zirconia and zirconia-mullite The present invention provides a method for producing a carbon-containing refractory slide plate, which comprises heat-treating a molded body for a slide plate, the molded body containing titanium carbide and / or metallic titanium in an outer percentage of 0.5 to 8 mass % relative to a main raw material composed of a refractory aggregate and a carbonaceous raw material, at atmospheric pressure in a nitrogen atmosphere having a nitrogen partial pressure of 0.85 atm or more when converted to a total atmospheric pressure of 1 atm, at a temperature of 400 to 1400°C.

[0025] In addition, the method for producing a carbon-containing slide plate refractory material of the present invention comprises the steps of: Refractory aggregate made of alumina and alumina-zirconia or made of alumina, alumina-zirconia and zirconia-mullite It is characterized by containing aluminum, silicon, magnesium, chromium or alloys thereof, silicon carbide, boron carbide, silicon nitride, and boron nitride in an amount of 8 mass% or less based on the main raw materials consisting of refractory aggregate and carbonaceous raw materials.

[0026] Furthermore, the method for producing a carbon-containing slide plate refractory material of the present invention is characterized in that the particle size of the titanium carbide and metallic titanium is 180 μm or less, and the heat treatment time is within the range of 3 to 30 hours. Effect of the Invention

[0027] According to the manufacturing method of the carbon-containing slide plate refractory of the present invention, it is possible to provide a carbon-containing slide plate refractory having not only sufficient mechanical strength and spalling resistance but also excellent corrosion resistance and hydration resistance. [Brief description of the drawings]

[0028] [Figure 1] (a) shows the results of an electron probe microanalyzer (EPMA) analysis of a titanium carbide-containing slide-plate refractory specimen (after heat treatment), and (b) shows the results of an electron probe microanalyzer (EPMA) analysis of a titanium metal-containing slide-plate refractory specimen (after heat treatment). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The method for producing a carbon-containing slide plate refractory material of the present invention is characterized in that a slide plate molding containing 0.5 to 8 mass% of titanium carbide and / or metallic titanium in terms of outer percentage relative to the main raw material composed of refractory aggregate and carbonaceous raw material is heat-treated under atmospheric pressure in a nitrogen atmosphere with a nitrogen partial pressure of 0.85 atm or more when converted to a total pressure of 1 atm.

[0030] By heat treating the molded body for slide plate containing titanium carbide and / or metallic titanium in a nitrogen atmosphere with a nitrogen partial pressure of 0.85 atm or more when converted to a total pressure of 1 atm, the titanium carbide and / or metallic titanium in the molded body easily take in nitrogen from the atmosphere, and generate in situ a nitrogen-containing phase containing titanium nitride such as titanium carbonitride or titanium nitride and containing 1 to 20 mass% of nitrogen element, thereby reducing the number of pores in the obtained slide plate refractory, reducing the pore diameter, and densifying the structure of the slide plate refractory. In addition, the nitrogen-containing phase itself is difficult to dissolve in molten steel and liquid inclusion slag in molten steel, and even if a small amount of the nitrogen-containing phase dissolves, the viscosity of the molten steel and liquid inclusion slag can be greatly increased.

[0031] The densified structure, low solubility and increased viscosity of such slide plate refractory make it difficult for molten steel and liquid inclusion slag in the molten steel to penetrate into the refractory, thereby significantly improving the corrosion resistance of the refractory to molten steel.

[0032] In addition, the nitrogen-containing phase does not react with water, so it does not cause hydration. Even when metallic aluminum is used in combination, metallic aluminum constantly absorbs nitrogen from the atmosphere through the nitrogen-containing phase that has already been formed during heat treatment and changes to aluminum nitride, so the formation of aluminum carbide is suppressed. The nitrogen-containing phase formed in situ is very active, and aluminum nitride is likely to be formed via the nitrogen-containing phase. As a result, even when metallic aluminum is used in combination, the slide plate refractory is unlikely to hydrate.

[0033] The nitrogen atmosphere in which the slide plate molded body is heat-treated may contain, in addition to the nitrogen component, components other than the nitrogen component, such as CO, CO2, H2, and H2O. In the heat treatment under atmospheric pressure, the nitrogen partial pressure of the nitrogen atmosphere is 0.85 atm or more, and preferably 0.90 atm or more, when the total pressure is converted to 1 atm.

[0034] Here, if the nitrogen partial pressure converted to a total atmospheric pressure of 1 atm is less than 0.85 atm, the titanium carbide and / or metallic titanium in the slide plate molding will not react with the nitrogen in the nitrogen atmosphere during heat treatment, and therefore a nitrogen-containing phase cannot be generated in situ. As a result, the resulting slide plate refractory will have insufficient corrosion resistance to molten steel and hydration resistance, which is undesirable.

[0035] The heat treatment temperature is 400 to 1400°C, preferably 500 to 1200°C. If the heat treatment temperature is less than 400°C, the nitrogen-containing phase is generated at a slow rate and in a small amount, so that the resulting slide plate refractory may have insufficient corrosion resistance against molten steel and hydration resistance. If the heat treatment temperature is more than 1400°C, the reaction of generating the nitrogen-containing phase is too fast, so that fine cracks are generated in the slide plate refractory during the heat treatment, and the corrosion resistance and hydration resistance may be reduced.

[0036] In the method for producing the carbon-containing slide plate refractory of the present invention, the slide plate molded body subjected to the heat treatment in a nitrogen atmosphere contains titanium carbide and / or metallic titanium in an amount of 0.5 to 8 mass%, preferably 1 to 6 mass%, based on the main raw material composed of the refractory aggregate and the carbon raw material. If the content of titanium carbide and / or metallic titanium is less than 0.5 mass%, the amount of the nitrogen-containing phase generated in situ is too small, and the corrosion resistance and hydration resistance of the obtained slide plate refractory to molten steel are insufficient, which is not preferable. If the content of titanium carbide and / or metallic titanium is more than 8 mass%, the amount of the nitrogen-containing phase generated in situ is too large, and the slide plate molded body may crack during the heat treatment, which is not preferable.

[0037] The raw material of titanium carbide and / or metal titanium to be added preferably has a particle size of 180 μm or less, more preferably 150 μm or less. If the particle size of the raw material of titanium carbide and / or metal titanium exceeds 180 μm, the particle size becomes too large, the rate of formation of the nitrogen-containing phase becomes slow, and the amount of the phase formed becomes small, so that the corrosion resistance against molten steel and the hydration resistance of the obtained slide plate refractory may become insufficient. Here, the "particle size" described in this specification is the particle size sieved by JIS Z8801-1 test sieve - Part 1: metal mesh sieve.

[0038] The heat treatment time is within a range of 3 to 30 hours, preferably 4 to 25 hours. Here, the heat treatment time refers to the total time during which the temperature range of 400°C or higher is passed. If the heat treatment time is less than 3 hours, the amount of nitrogen-containing phase generated in situ is too small, and the corrosion resistance and hydration resistance of the resulting slide plate refractory to molten steel may become insufficient. If the heat treatment time exceeds 30 hours, the heat treatment effect is saturated, which is economically undesirable.

[0039] Here, the raw material of titanium carbide to be added to the mixture for producing the slide plate molded body can be titanium carbide alone, titanium-containing composite carbides and carbonitrides, for example, composite carbides and carbonitrides consisting of titanium and one or more of aluminum, silicon, zirconium, chromium, nickel, molybdenum, tungsten, boron, etc. When titanium-containing composite carbides and carbonitrides are used, they are used in an amount such that the titanium carbide content is in the range of 0.5 to 8 mass%.

[0040] Furthermore, as the raw material of metallic titanium to be added to the mixture for producing the molded body for a slide plate, metallic titanium alone, a titanium-containing alloy, for example, an alloy consisting of one or more of titanium and aluminum, silicon, magnesium, iron, manganese, nickel, copper, zirconium, chromium, molybdenum, tungsten, boron, etc., and a titanium compound, for example, titanium hydride, etc. When a titanium alloy or a titanium compound is used, it is used in an amount such that the titanium content is in the range of 0.5 to 8 mass% in terms of titanium carbide.

[0041] The mixture for producing the slide plate molded body is composed of a refractory aggregate and a carbonaceous raw material as main raw materials, and the refractory aggregate is not particularly limited, and for example, conventional raw materials such as alumina, magnesia, zirconia, alumina-zirconia, zirconia-mullite, spinel, and mullite can be used alone or in combination. These raw materials can be used as sintering raw materials or electric melting raw materials.

[0042] Furthermore, as the carbonaceous raw material constituting the main raw material, for example, carbon black, pitch, coke, natural graphite, artificial graphite, etc. can be used alone or in combination.

[0043] The ratio of the refractory aggregate to the carbonaceous raw material is in the range of 1-10% by mass, preferably 2-8% by mass. If the ratio of the carbonaceous raw material is less than 1% by mass, the spalling resistance of the resulting slide plate refractory may decrease. If the ratio of the carbonaceous raw material is more than 10% by mass, the in-situ generation of the nitrogen-containing phase may be inhibited.

[0044] In addition, for the purpose of further improving the oxidation prevention effect of the carbonaceous raw material and the mechanical strength of the slide plate refractory, metals such as aluminum, silicon, magnesium, chromium, etc. or their alloys, carbides such as silicon carbide and boron carbide, and nitrides such as silicon nitride and boron nitride can be appropriately blended into the slide plate molded body. The content of these components is 8% by mass or less, preferably 6% by mass or less, based on the main raw material composed of the refractory aggregate and the carbonaceous raw material. If the content of these components exceeds 8% by mass, based on the main raw material composed of the refractory aggregate and the carbonaceous raw material, the effect of the nitrogen-containing phase generated in situ may decrease.

[0045] Furthermore, the molded body for slide plate may contain tar, phenol resin, etc. as a binder. The amount of these binders added is not particularly limited, and may be a conventional amount, that is, within the range of 1 to 10 mass %, preferably 2 to 8 mass %, based on the total amount of the above components constituting the molded body for slide plate.

[0046] The slide plate molded body used in the method for producing the carbon-containing slide plate refractory material of the present invention can be obtained by adjusting the above-mentioned raw materials in a predetermined mixing ratio, kneading the mixture obtained, molding the mixture into a predetermined shape, and drying it.

[0047] The slide plate refractory obtained by the method for producing a carbon-containing slide plate refractory of the present invention can be applied to the entire plate, but can also be applied to only a part of the plate, for example, only near the working surface that comes into contact with molten steel. EXAMPLES

[0048] Example 1 A molded body for slide plate was prepared with the blending ratios shown in Tables 1 to 8 below, and various carbon-containing slide plate refractory specimens were obtained by performing heat treatment under atmospheric pressure under the heat treatment conditions shown in Tables 1 to 8. The obtained specimens were subjected to hydration resistance evaluation tests and corrosion resistance evaluation tests. In addition, when preparing the molded body for slide plate, phenolic resin was used as a binder in an outer amount of 4 mass%, and a hydraulic press method was used for molding. In addition, the nitrogen partial pressure (atm) of the nitrogen atmosphere indicates the nitrogen partial pressure when the total atmospheric pressure is converted to 1 atm. The "hydration resistance evaluation test" used a cube with a side length of 50 mm as a test specimen, and used an autoclave to hold the specimen at 154°C for 8 hours under a pressure of 0.51 MPa, and then measured the mass increase rate of the specimen before and after the test. The smaller the mass increase rate, the smaller the degree of hydration of the specimen and the higher its hydration resistance; The "corrosion resistance evaluation test" used a specimen measuring 25 mm wide x 25 mm wide x 250 mm high, and was performed by immersing the specimen in argon atmosphere in a high-frequency furnace at 1560°C for 5 hours after melting calcium-treated steel (Ca content = 40 ppm). After the test, the width of the immersed part of the specimen was measured, and the change in the specimen width before and after the test was recorded as the amount of corrosion loss. The smaller the amount of corrosion loss, the higher the corrosion resistance. The "overall judgment" was made based on a comprehensive assessment of the hydration resistance evaluation test and the corrosion resistance evaluation test. A "◎" was given to a case in which both the hydration resistance evaluation test and the corrosion resistance evaluation test were excellent, a "○" was given to a case in which either of them tended to be slightly inferior, a "△" was given to a case in which some of the results of both evaluation tests were inferior but within the acceptable range, and an "×" was given to a case in which either or both of these evaluation tests were inferior. The results are shown in Tables 1 to 8.

[0049] Tables 1 and 2 show the effect of the nitrogen partial pressure of the nitrogen atmosphere in the examples of the present invention and the comparative examples. Table 3 shows the effect of the amount of titanium carbide added in the examples of the present invention and the comparative examples. Table 4 shows the effect of the titanium carbide particle size in the examples of the present invention. Table 5 shows the effect of the maximum temperature of the heat treatment in the examples of the present invention. Table 6 shows the effect of the heat treatment time in the examples of the present invention. Table 7 shows an example of the present invention using a titanium alloy. As the titanium alloy, a titanium-aluminum alloy with a titanium content of 45 mass% was used. Table 8 shows an example of the present invention using alumina, alumina-zirconia, and zirconia-mullite in combination as the refractory aggregate, and an example of the present invention not containing metallic aluminum or metallic silicon.

[0050] [Table 1]

[0051] [Table 2]

[0052] [Table 3]

[0053] [Table 4]

[0054] [Table 5]

[0055] [Table 6]

[0056] [Table 7]

[0057] [Table 8]

[0058] The microstructure of the specimen (after heat treatment) of Example 2 of the present invention was analyzed by an electron probe microanalyzer (EPMA) and is shown in Figure 1(a). It was confirmed that the titanium carbide contained 63.7% by mass of titanium, 26.9% by mass of carbon, and 9.4% by mass of nitrogen, and that a nitrogen-containing phase containing 1 to 20% by mass of nitrogen was present. It was also confirmed that the metallic aluminum contained in the mixture was changed to a mineral phase composed of nitrogen, aluminum, and the like. Furthermore, the results of the microstructure obtained by the electron probe microanalyzer (EPMA) analysis of the specimen (after heat treatment) of Example 5 of the present invention are shown in Figure 1 (b). It was confirmed that the mixed metallic titanium was changed to a nitride with a titanium content of 83.6 mass% and a nitrogen content of 16.4 mass%, and that a nitrogen-containing phase containing 1 to 20 mass% of nitrogen was present. It was also confirmed that the metallic aluminum used in combination was changed to a mineral phase composed of nitrogen, aluminum, etc. It was also confirmed that the test specimens obtained in other examples of the present invention also contained a nitrogen-containing phase containing 1 to 20 mass % nitrogen. Furthermore, in Examples 30 to 33 of the present invention, which used a titanium-aluminum alloy, it was confirmed that both the titanium and aluminum that constitute the titanium-aluminum alloy were changed to a mineral phase composed of nitrogen and aluminum, etc., and a nitrogen-containing phase containing 1 to 20 mass % of nitrogen element including titanium nitrides such as titanium carbonitride and titanium nitride.

[0059] As is clear from the results shown in Tables 1 to 8, the test specimens obtained by the method of the present invention had significantly higher hydration resistance and corrosion resistance than the comparative examples. Furthermore, the test specimens obtained by the method of the present invention had sufficient mechanical strength and spalling resistance.

[0060] Example 2 The carbon-containing slide plate refractory obtained in Example 2 of the present invention in Table 1 was used as a ladle slide plate refractory for casting calcium-treated steel in an actual plant. The service life of the ladle slide plate refractory made of the carbon-containing slide plate refractory obtained in Comparative Example 1 was 4ch, whereas the service life of the ladle slide plate refractory made of the carbon-containing slide plate refractory obtained in Example 2 of the present invention reached 6ch. In addition, the carbon-containing slide plate refractory obtained in Example 2 of the present invention did not develop any cracks even when left in a place with a high humidity of 70% or more for about two years, but the carbon-containing slide plate refractory obtained in Comparative Example 1 developed many large cracks. [Industrial Applicability]

[0061] The carbon-containing slide plate refractory obtained by the method of the present invention has sufficient mechanical strength and spalling resistance, and at the same time, has excellent corrosion resistance and hydration resistance, and is therefore highly applicable in the steel industry.

Claims

1. A method for producing a carbon-containing slide plate refractory material, comprising heat-treating a molded body for a slide plate, the molded body comprising a refractory aggregate made of alumina and alumina-zirconia, or a refractory aggregate made of alumina, alumina-zirconia, and zirconia-mullite, and a carbonaceous raw material as a main raw material, with titanium carbide and / or metallic titanium being contained in an outer percentage of 0.5 to 8 mass % relative to the main raw material, the outer percentage being 0.5 to 8 mass % relative to the main raw material, the carbonaceous raw material being contained in a nitrogen atmosphere having a nitrogen partial pressure of 0.85 atm or more when the total pressure is converted to 1 atm, at a temperature of 400 to 1400°C under atmospheric pressure.

2. 2. The method for producing a carbon-containing slide plate refractory material according to claim 1, wherein the slide plate molded body contains aluminum, silicon, magnesium, chromium or alloys thereof, silicon carbide, boron carbide, silicon nitride, or boron nitride in an amount of 8 mass% or less in terms of outer percentage based on a main raw material composed of a refractory aggregate made of alumina and alumina-zirconia or a refractory aggregate made of alumina, alumina-zirconia, and zirconia-mullite and a carbonaceous raw material.

3. 2. The method for producing a carbon-containing slide plate refractory material according to claim 1, wherein the particle size of the titanium carbide and the titanium metal is 180 μm or less.

4. The method for producing a carbon-containing slide plate refractory material according to any one of claims 1 to 3, wherein the heat treatment time is within a range of 3 to 30 hours.

Citation Information

Patent Citations

  • Refractory

    JP1980034665A

  • Plate refractories for sliding nozzle

    JP1983099161A

  • Nitride bonded refractory and its production

    JP1995101768A

  • Carbon-containing refractory

    JP1995172907A

  • Plate for slide gate and its production

    JP1999199313A